Harmonic interaction of a static Var compensator with AC power system containing multiple non-linear loads - Nassim Kraimia, Mohamed (Array, 2020)
In this paper a study of the impact of the harmonics generated by a static Var compensator (SVC) is presented. The SVC is modeled, in the harmonic domain, as a coupled current source by using the complex Fourier transforms. Then, this model is converted to polar form to be integrated into the harmonic power flow program. This approach has been carried out on the IEEE 14 bus test power system, in order to show its effectiveness in evaluating the impact of harmonics, injected by the shunt compensating devices, and its interaction with the AC transmission system, in meshed power networks. Since the SVC consists of a thyristorcontrolled reactor (TCR) and a fixed capacitor, the harmonic currents are functions of the TCR thyristors firing angles. The variation of the total voltage harmonic distortion as function of firing angle changes and location of nonlinear loads is clearly presented and discussed.